2018
DOI: 10.3389/fnhum.2018.00293
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Background Music on Inhibitory Functions: An ERP Study

Abstract: The influence of background music on cognitive functions is still a matter of debate. In this study, we investigated the influence of background music on executive functions (particularly on inhibitory functions). Participants completed a standardized cued Go/NoGo task during three different conditions while an EEG was recorded (1: with no background music, 2: with relaxing, or 3: with exciting background music). In addition, we collected reaction times, omissions, and commissions in response to the Go and NoG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
4
15
2
2
Order By: Relevance
“…Because our study used normative loudness sound (50 dB) stimulation, instead of loud sound (95 dB) as in Keil’s study, the present results expand the knowledge that appraisal response to everyday level loudness sound could also be modulated by background music. Contrary to our findings, a study addressing the effects of similar background music conditions (excited background music, relax background music, and NoBGM) on cognitive inhibitory function reported that N2d and P3 component amplitudes are not affected (Burkhard et al, 2018). These findings suggest that the interference of background music might be a cognitive function specific, although this idea awaits further examination.…”
Section: Discussioncontrasting
confidence: 99%
“…Because our study used normative loudness sound (50 dB) stimulation, instead of loud sound (95 dB) as in Keil’s study, the present results expand the knowledge that appraisal response to everyday level loudness sound could also be modulated by background music. Contrary to our findings, a study addressing the effects of similar background music conditions (excited background music, relax background music, and NoBGM) on cognitive inhibitory function reported that N2d and P3 component amplitudes are not affected (Burkhard et al, 2018). These findings suggest that the interference of background music might be a cognitive function specific, although this idea awaits further examination.…”
Section: Discussioncontrasting
confidence: 99%
“…Another finding of the present study is that no significant difference was observed in the N400 effect between the high- and low-arousal music groups, consistent with Burkhard et al 39 who showed no different effects on inhibitory function between the relaxing and exciting background music conditions. This finding could be attributed to the constant arousal levels of our participants during the entire experiment.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, even during face encoding, no differences in cortical activity between the background music and silence conditions were found 38 . The absence of the effect of background music is consistent with a recent study suggesting that background music has no effect on inhibitory functions, as evidenced by no differences in influences on inhibitory functions among relaxing, exciting background music and silence conditions at both the behavioural and electrophysiological levels 39 . To date, however, little is known about how the brain works when reading tasks are accompanied by background music or not.…”
Section: Introductionsupporting
confidence: 90%
“…Comparing the differences between the three plateau groups and one plain group revealed that the three plateau groups' soldiers showed a significant decrease in amplitude both in the N2 component of conflict monitoring and the P3 component of late processing of information. Studies have indicated that N2 and P3 are considered to function as separable processes in Go/NoGo tasks (Randall and Smith, 2011;Burkhard et al, 2018). The NoGo-N2 component response conflict detection and response inhibition can effectively represent the soldiers' cognitive control degree (Enriquez-Geppert et al, 2010;Burkhard et al, 2018).…”
Section: Changes In Response Inhibition Function In Soldiers From Difmentioning
confidence: 99%
“…Studies have indicated that N2 and P3 are considered to function as separable processes in Go/NoGo tasks (Randall and Smith, 2011;Burkhard et al, 2018). The NoGo-N2 component response conflict detection and response inhibition can effectively represent the soldiers' cognitive control degree (Enriquez-Geppert et al, 2010;Burkhard et al, 2018). The NoGo-P3 component amplitude is associated with late processing of response inhibition (Groom and Cragg, 2015).…”
Section: Changes In Response Inhibition Function In Soldiers From Difmentioning
confidence: 99%